2018
DOI: 10.1002/cam4.1514
|View full text |Cite
|
Sign up to set email alerts
|

A novel plasma circular RNA circFARSA is a potential biomarker for non‐small cell lung cancer

Abstract: Emerging evidence indicates that circular RNAs (circRNAs) are implicated in cancer development. This study aimed to evaluate whether circulating circRNAs may serve as novel biomarkers for non‐small cell lung cancer (NSCLC). We used RNA sequencing (RNA‐seq) and quantitative real‐time PCR to explore cancer‐related circRNAs. Bioinformatics and functional analyses were performed to reveal biological effects of circRNAs on lung cancer cells. A total of 5471 distinct circRNAs were identified by total RNA‐seq, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
114
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 33 publications
3
114
0
Order By: Relevance
“…Some recent studies have implied that non‐coding RNAs, especially circRNAs, play crucial roles in pathology and progression of NSCLC . For example, long non‐coding RNA KDM5B anti‐sense RNA 1 enhances tumor progression in NSCLC; circular RNA F‐circSR derived from SLC34A2‐ROS1 fusion gene enhances cell migration in NSCLC; overexpression of circular RNA FARSA promotes NSCLC cell migration and invasion . According to these indications, we speculated that circ‐SMARCA5 might also have suppressive effect in NSCLC.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Some recent studies have implied that non‐coding RNAs, especially circRNAs, play crucial roles in pathology and progression of NSCLC . For example, long non‐coding RNA KDM5B anti‐sense RNA 1 enhances tumor progression in NSCLC; circular RNA F‐circSR derived from SLC34A2‐ROS1 fusion gene enhances cell migration in NSCLC; overexpression of circular RNA FARSA promotes NSCLC cell migration and invasion . According to these indications, we speculated that circ‐SMARCA5 might also have suppressive effect in NSCLC.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have demonstrated that circRNAs may be closely connected with the development cancers . Among them, circ‐SMARCA5, the circRNA derives from exons 15 and 16 of SMARCA5 gene, is found to be related to the disease progression in a few cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent reports revealed that circRNAs may be involved in several cellular and developmental process of some diseases, such as prion diseases, neurological disorders, atherosclerotic vascular disease risk, as well as different malignant tumours . It is reported that circRNAs could function as potential disease biomarkers in human saliva and as biomarkers for non‐small cell lung cancer and ageing . However, the possible involvement of circRNAs in the pathogenesis of COPD remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, circRNAs were found to be involved in the tumorigenesis of NSCLC, recently [22]. For example, a total of 185 circRNAs were detected to be dysregulated by an RNA sequencing performed by Hongbing Shen et al in 10 pairs NSCLC and normal samples, among which circFARSA expression was found to be increased in NSCLC tissues and patients' plasma, suggesting that circFARSA might act as a potential non-invasive biomarker for NSCLC [23]. In this study, we focus on a circRNA microarray to detect the circRNA expression profile of NSCLC samples and paired normal samples to better characterize the relationship between circRNAs expression and NSCLC and to offer a preliminary theoretical basis for a search of biomarkers for the early diagnosis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%